Effect of early strength agent on the hydration of geopolymer mortar at low temperatures - Tao Chen; Biao Ren; Zhihang Wang; Xin Meng; Yipeng Ning; Yan Lv (Case Studies in Construction Materials, 2022)
In order to study the hydration law of geopolymer mortar in low temperature environment and explore the early strength agent suitable for geopolymer mortar in low temperature environment, this paper studied the development of compressive strength, flexural strength and hydration temperature of slag silica fume based geopolymer mortar at 10 ℃ when lithium carbonate, triethanolamine and triisopropylamine (TIPA) were added respectively. The hydration reaction process and micro mechanism of slag silica fume based geopolymer mortar with early strength agent at low temperature were analyzed by SEM and FTIR. The results show that lithium carbonate, triethanolamine and TIPA can enhance the early mechanical properties of slag silica fume based geopolymer mortar, and the strengthening effect is related to the content of early strength agent. The optimum contents of triethanolamine, TIPA and lithium carbonate are 0.06%, 0.04% and 0.4% respectively, and triethanolamine has the best reinforcing effect. Adding early strength agent can promote the secondary hydration of geopolymer mortar and accelerate the formation of hydration products. The early strength agent can improve the microstructure of slag silica fume based geopolymer mortar and make the mortar more dense and stronger.